2001
DOI: 10.1128/aem.67.8.3463-3468.2001
|View full text |Cite
|
Sign up to set email alerts
|

Brown Pigments Produced by Yarrowia lipolytica Result from Extracellular Accumulation of Homogentisic Acid

Abstract: Yarrowia lipolytica produces brown extracellular pigments that correlate with tyrosine catabolism. During tyrosine depletion, the yeast accumulated homogentisic acid, p-hydroxyphenylethanol, and p-hydroxyphenylacetic acid in the medium. Homogentisic acid accumulated under all aeration conditions tested, but its concentration decreased as aeration decreased. With moderate aeration, equimolar concentrations of alcohol and p-hydroxyphenylacetic acid (1:1) were detected, but with lower aeration the alcohol concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
1
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 32 publications
4
47
1
6
Order By: Relevance
“…Melanins are also broadly distributed among eukaryotic microorganisms, including fungi and protozoa (70,79 (4,29,33,42,45,55,64,90,102). Among the eukaryotic microbes, endogenous HGA-melanin production is thus far limited to the fungi Aspergillus nidulans and Yarrowia lipolytica (13,36), although it has recently been shown that the fungus Cryptococcus neoformans can use HGA produced by others to achieve melanization (38). Thus, L. pneumophila, along with P. aeruginosa and V. cholerae, is one of the few known producers of HGAmelanin that is also a significant human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Melanins are also broadly distributed among eukaryotic microorganisms, including fungi and protozoa (70,79 (4,29,33,42,45,55,64,90,102). Among the eukaryotic microbes, endogenous HGA-melanin production is thus far limited to the fungi Aspergillus nidulans and Yarrowia lipolytica (13,36), although it has recently been shown that the fungus Cryptococcus neoformans can use HGA produced by others to achieve melanization (38). Thus, L. pneumophila, along with P. aeruginosa and V. cholerae, is one of the few known producers of HGAmelanin that is also a significant human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Oprócz produkcji amin biogennych kolejną niepożądaną cechą drożdży, negatywnie wpływającą na jakość dojrzałego sera, jest ich zdolność do produkcji barwników melaninowych, związków o charakterze polifenolowych heteropolimerów, któ-rych prekursorem jest nagromadzona w środowisku tyrozyna [2]. Hodowle na agarze serowym wzbogaconym tyrozyną wykazały, że żaden z badanych szczepów D. hasenii nie produkował pigmentu, niezależnie od temperatury inkubacji.…”
Section: Wyniki I Dyskusjaunclassified
“…: owocowy, gorzki, drożdżowy posmak czy gazowanie masy serowej [8]. Ponadto, wiele gatunków drożdży wykazuje swoisty szlak enzymatycznej konwersji obecnej w śro-dowisku sera tyrozyny do związków pośrednich, które ulegając spontanicznej oksydacji i polimeryzacji, pojawiają się na powierzchni sera w postaci brunatnych barwników melaninowych [2].W wielu ośrodkach naukowych trwają badania nad stworzeniem jedno-, dwu-lub wielogatunkowych drożdżowych szczepionek serowarskich. Do drożdży wykazują-cych wiele pożądanych cech fizjologicznych, a jednocześnie gwarantujących bezpieczeństwo konsumenta (statut GRAS) zaliczane są m.in.…”
unclassified
See 2 more Smart Citations